Culture, Conflict, and Counterinsurgency - Johnson, Thomas H.; Zellen, Barry Scott, 1963- (Stanford Security Studies, 2014)
The authors of Culture, Conflict and Counterinsurgency contend that an enduring victory can still be achieved in Afghanistan. However, to secure it we must better understand the cultural foundations of the continuing conflicts that rage across Afghanistan and neighboring Pakistan, and shift our strategy from an attritional engagement to a smarter war plan that embraces these cultural dimensions. They examine the nexus of culture, conflict, and strategic intervention, and attempt to establish if culture is important in a national security and foreign policy context, and to explore how cultural phenomena and information can best be used by the military. In the process they address just how intimate cultural knowledge needs to be to counter an insurgency effectively. Finally, they establish exactly how good we've been at building and utilizing cultural understanding in Afghanistan, what the operational impact of that understanding has been, and where we must improve to maximize our use of cultural knowledge in preparing for and engaging in future conflicts.--